2014
DOI: 10.1002/app.40480
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation behavior and gas phase flame‐retardant mechanism of polylactide/PCPP blends

Abstract: The thermal degradation behavior of the blend based on polylactide (PLA) and poly(1,2-propanediol 2-carboxyethyl phenyl phosphinate) (PCPP) was investigated by the thermogravimetric analysis (TGA). Thermal degradation activation energies (E a ) of neat PLA and PLA/15% PCPP blend were calculated via the Flynn-Wall-Ozawa method. The E a of the blends increased with the addition of PCPP increasing when the conversion was higher than 10%. In addition, the appropriate conversion models for the thermal degradation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…Moreover, decomposition of polylactide in presence of phosphorus-based polymer was studied and similar conclusion was addressed [52]. This type of polymeric flame retardant is expected to decompose and produce active radicals, quenching of flammable volatiles.…”
Section: Pyrolysis-gas Chromatography (Py-gc)mentioning
confidence: 81%
See 2 more Smart Citations
“…Moreover, decomposition of polylactide in presence of phosphorus-based polymer was studied and similar conclusion was addressed [52]. This type of polymeric flame retardant is expected to decompose and produce active radicals, quenching of flammable volatiles.…”
Section: Pyrolysis-gas Chromatography (Py-gc)mentioning
confidence: 81%
“…The thermal behavior of a polymer can be affected by the incorporation of an additive (e.g., flame retardant). Thereby, TGA analysis is a fast and efficient way to analyze the effect of the additive on the polymer matrix [14,[51][52][53]. However, TGA analysis alone is not enough to detect species evolved during the thermal decomposition of material.…”
Section: Coupled Thermal Techniques (Tga-ms/ftir)mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that the molten mass drip from the matrix had taken out heat generation during combustion, and led to flame extinguishment. In a follow-up paper Lin et al [66] studied the thermal degradation behavior of the blend composed of PLA and PCPP (added in 15 wt%) by TGA, TGA-FTIR and pyrolysis gas chromatography-mass spectrometry analysis. The activation energy of thermal degradation, calculated by the Flynn-Wall-Ozawa method, increased in the presence of PCPP when the degradation conversion was higher than 10%.…”
Section: Poly(lactic Acid) With Novel Synthesizedmentioning
confidence: 99%
“…the depletion of petroleum reserves (the feedstock for conventional plastics) and the environmental harm caused by the irresponsible disposal of non-degradable polymers [4,5]. Nowadays, PLA is more progressively used in fibres and fabrics applications [6,7] because it can be spun by using techniques such as solution spinning, electrospinning and melt spinning [8,9].…”
Section: Introductionmentioning
confidence: 99%